Knee ligament injuries in alpine skiing - the mechanism of injury and the possibilities of using modern knowledge and technology to prevent injuries in skiing - Niski, Szymon; Żaba, Ziemowit; Milczek, Maria; Warzyszak, Paweł; Żołyniak, Wojciech; Tomasik, Mikołaj; Hawranik, Izabela; Małek, Róza; Lisowska, Aleksandra; Skrzypek, Mateusz (Quality in Sport, 2023)
Introduction: Over the years, advances in alpine ski equipment such as helmets, bindings, skis and boots have resulted in risk reduction, remodelling of injury patterns and mechanisms. Skiers’ injuries are currently about 1 to 5 per 1000 days spent in the snow per athlete. The most common area of the injury is the knee, especially ACL and MCL. Purpose of the work: The purpose of the work is analysis of literature on mechanism of knee ligaments injury and potential prevention intervention in alpine skiing. Methods and materials: The present study was based on available data collected in the PubMed and Google Scholar database. The study was conducted by reviewing keywords such as: “alpine skiing”, “ski bindings”, “alpine skiing injuries”, “ACL”. Results: Taking into consideration less advanced skiers, we can distinguish three types of injury mechanism: valgus-external rotation sequence, boot-induced anterior drawer mechanism and phantom-foot mechanism. Three mechanisms have been described for professional skiers: slip-catch, landing back-weighted and dynamic snowplow. Female skiers have a higher risk of ACl injury than male skiers. Conclusion: Most of the described injury mechanisms are linked with no releasing of bindings. The future injury prevention should concentrate on injury mechanisms using electronic sensors placed at skiers equipment. New micro-electronic technologies can help create mechatronic ski bindings.